A systematic review of the unmet supportive care needs of men on active surveillance for prostate cancer. Issue 12 (6th November 2019) - McIntosh, Megan; Opozda, Melissa J.; Evans, Holly; Finlay, Amy; Galvão, Daniel A.; Chambers, Suzanne K.; Short, Camille E.
Abstract: Objective: Understanding the unmet supportive care needs of men on active surveillance for prostate cancer may enable researchers and health professionals to better support men and prevent discontinuation when there is no evidence of disease progression. This review aimed to identify the specific unmet supportive care needs of men on active surveillance. Methods: A systematic review following PRISMA guidelines was conducted. Databases (Pubmed, Embase, PsycINFO, and CINAHL) were searched to identify qualitative and/or quantitative studies that reported unmet needs specific to men on active surveillance. Quality appraisals were conducted before results were narratively synthesised. Results: Of the 3613 unique records identified, only eight articles were eligible (five qualitative and three cross‐sectional studies). Unmet Informational, Emotional/Psychological, Social, and "Other" needs were identified. Only three studies had a primary aim of investigating unmet supportive care needs. Small active surveillance samples, use of nonvalidated measures, and minimal reporting of author reflexivity in qualitative studies were the main quality issues identified. Conclusions: The unmet needs of men on active surveillance is an underresearched area. Preliminary evidence suggests the information available and provided to men during active surveillance is perceived as inadequate and inconsistent. Men may also be experiencing unmet psychological/emotional, social, and other needs; however, further representative, high‐quality research is required to understand the magnitude of this issue. Reporting results specific to treatment type and utilising relevant theories/models (such as the social ecological model [SEM]) is recommended to ensure factors that may facilitate unmet needs are appropriately considered and reported.